আমলাগাছি - মিশ্র, ভগীরথ, ১৯৪৭- (কলকাতা : দে'জ পাবলিশিং, 2017)
Autobiographical reminiscences of Bhagīratha Miśra, b. 1947, Bengali author and retired government officer of West Bengal, India.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Miśra, Bhagīratha, -- 1947-; Authors, Bengali -- India -- West Bengal -- Biography; Authors, Bengali -- 20th century -- Biography; West Bengal (India) -- Officials and employees -- Biography